AWARENESS, TREATMENT AND CONTROL OF HYPERTENSION IN GREECE: THE EMENO NATIONAL EPIDEMIOLOGICAL STUDY. (April 2021) - Stergiou, George; Menti, Ariadni; Kalpourtzi, Natasa; Gavana, Magdalini; Vantarakis, Apostolos; Chlouverakis, Gregory; Hadjichristodoulou, Christos; Trypsianis, Gregory; Voulgari, Paraskevi; Alamanos, Yannis; Karakosta, Argiro; Touloumi, Giota
Abstract : Objective: The evidence on the epidemiology of hypertension in Greece is limited. The EMENO nationwide epidemiological study assessed the prevalence, awareness, treatment and control of hypertension in randomly selected adults in the general population in Greece. Design and method: EMENO applied a multi-stage stratified random sampling method involving 577 areas throughout Greece from May 2013 to June 2016. Participants were assessed at homes visits with standardized questionnaires, blood tests and 3 seated blood pressure (BP) measurements (validated upper-arm oscillometric device Microlife BPA100 Plus). Hypertension was defined as BP >=140/90 mmHg (average of 2nd-3rd measurement) and/or use of antihypertensive drugs). Post-stratification weights were applied in order to match the age/sex distribution to the general population in Greece based on census 2011. Non-response was adjusted by inverse probability weighting. Results: A total of 6, 006 subjects were recruited and 4, 699 with complete data were analysed (mean age 49.0 ± 18.5 [SD]) years, men 48.5%, BMI 28.1 ± 5.7 kg/m 2 ). The prevalence of HT was 39.2% and was higher in men than women (42.4% vs. 36.1%, p < 0.001). Among hypertensive patients, 32.0% were unaware (men/women 39.7/23.7, p < 0.001), 2.7% aware untreated, 34.9% treated uncontrolled (men/women 31.8/38.2, p < 0.001) and 30.4% treated controlled (men/women 25.7/35.6, p < 0.001). Conclusions: More than one third of the adults in the general population in Greece have elevated BP. One third of them are undiagnosed and only 30.4% are controlled with treatment. Nationwide programs are needed to prevent hypertension and improve its awareness and control in Greece.